The C-type Lectin Receptor-Driven, Th17 Cell-Mediated Severe Pathology in Schistosomiasis: Not All Immune Responses to Helminth Parasites Are Th2 Dominated - Kalantari, Parisa; Bunnell, Stephen C.; Stadecker, Miguel J. (Frontiers in Immunology, 2019)
Schistosomiasis is a major helminthic disease in which damage to the affected organs is orchestrated by a pathogenic host CD4 T helper (Th) cell-mediated immune response against parasite eggs. In the case of the species Schistosoma mansoni, the resulting granulomatous inflammation and fibrosis takes place in the liver and intestines. The magnitude of disease varies greatly from individual to individual but in a minority of patients there is severe disease and death. S. mansoni infection in a murine model similarly results in marked strain variation of immunopathology. In the most commonly examined mouse strain, C57BL/6 (BL/6), there is relatively mild hepatic pathology arising in a Th2-dominated cytokine environment. In contrast, CBA mice develop decisively more severe lesions largely driven by proinflammatory IL-17-producing Th17 cells. Dendritic cells (DCs) from CBA mice differ sharply with those from BL/6 mice in that they vastly over-express the C-type lectin receptor (CLR) CD209a (SIGNR5), a homolog of human DC-SIGN, which senses glycans such as those produced by schistosome eggs. Silencing of CD209a, and recent studies with CD209a KO CBA mice have shown that this receptor is crucial to induce the pathogenic Th17 cell response; indeed, CD209a KO mice display markedly reduced immunopathology akin to that seen in BL/6 mice. Mechanistically, CD209a synergizes with the related CLRs Dectin-2 and Mincle to stimulate increased DC production of IL-1β and IL-23, necessary for pathogenic Th17 cell development. These findings reveal key molecular underpinnings of disease variability based on selection and function of contrasting Th cell subsets.